A geographical study of M̄2(P2,4)main - Battistella, Luca; Carocci, Francesca (Arxiv, 2021)
We discuss criteria for a stable map of genus two and degree $4$ to the projective plane to be smoothable, as an application of our modular desingularisation of $\overline{\mathcal M}_{2,n}(\mathbb{P}^r,d)^{\text{main}}$ via logarithmic geometry and Gorenstein singularities.